UJI UNJUK KERJA ALAT IRIGASI SPRINKLER TIPE GUN RAIN DN-50 DI DESA TONTALETE KECAMATAN KEMA KABUPATEN MINAHASA UTARA - Meike C. Kusaly; Ruland A. Rantung; Dedie Tooy (Universitas Sam Ratulangi, 2021)
Abstract This study aims to test the performance of irrigation sprinkler type gun rain DN-50, and how to manage water efficiently and effectively through the use of pressurized irrigation technology on plantation land located in Tontalete Village. This study uses tools such as sprinklers and water pumps on soybean plantations in Tontalete Village with an area of 60m x 60m. The results of this study indicate of watering using irrigation sprinkler the type Gun Rain DN-50 at the Village Tontalete for 19 minutes with 3 rounds of sprinkler produces 3.254 l and wet land 1808.64 m2, uniformity coefficient values indicating that the level of use watering sprinkler less efficient, the low rotational value of the pump (rpm) that is not in accordance with the specifications, and the sprinkler transmission distance which only reaches 24 m. Keywords: performance test,tools of irrigation, sprinkler, water supply, coefficient uniformity.